Avaliação da atividade vascular do D-Pinitol em artéria mesenterica - Luciana Nascimento Moreira (2015)
D-pinitol (3-O-methyl-D-chiro-inositol) is a cyclitol present in several plant species (citrus fruits and vegetables). Recent studies demonstrated the ability of this cyclitol in reversing the endothelial dysfunction and to inhibit the release of pro-inflammatory cytokines in animal models of diabetes mellitus. In humans, D-pinitol shows hypoglycemic activity and reduces systolic and diastolic blood pressure in individuals with type II diabetes mellitus. Considering the importance of cardiovascular diseases in the morbidity and mortality associated with diabetes mellitus, the effects described for the D-pinitol suggest a protective effect of this drug in the cardiovascular system. The present work aimed at investigating the mechanisms involved in the vascular effects of D-pinitol in mouse mesenteric artery. Male mice C57BL/6 with 8-14 weeks were used (Animal Ethics Committees: Protocol 170/2014). Mesenteric arteries 2nd branch were dissected and sectioned in 1.6 to 2.0 mm rings. These segments were mounted in a wire myograph (DMT, Aarhus, Denmark). D-pinitol induced a concentration-dependent vasodilation in the presence of a functional endothelium. This vasodilator effect was abolished in the absence of a functional endothelium and in the presence of L-NAME (300 M), a nonselective inhibitor of nitric oxide synthase (NOS). In arteries treated with ODQ (10 M), an inhibitor of guanylate cyclase, the concentration-effect curve was shifted to the right. D-pinitol significantly increased the nitrite production in mesenteric arteries with a functional endothelium. This effect was inhibited by L-NAME and calmidazolium (10 M), an inhibitor of calmodulin. D-pinitol significantly increased the phosphorylation level of NOS at Ser1177, activation site, and reduced the phosphorylation level at Thr495, inactivation site. The present results led us to conclude that the Dpinitol has an endothelium- and NOS- and NO-dependent vasodilator effect in mouse mesenteric artery activated by a mechanism dependent on calcium-calmodulin.